Analisa Teknoekonomi Biogas Dari Eceng Gondok dengan Stater Kotoran Sapi - Meylinda Mulyati (Polinema Press, Politeknik Negeri Malang, 2018)
Water hyacinth is a waste that can be utilized by the community as an alternative potential for biogas energy. The formation of biogas from water hyacinth requires a residence time (LT) that is still long, which is between 30-35 days for the formation of methane. So that the process of forming methane is not too long, a stater is needed so that methanogenic bacteria can increase from cow dung so that the residence time is much shorter. The process of making biogas starts from making a digester, the process of taking water hyacinth by chopping water hyacinth, preparing cattle dung stater. The purpose of this study is to analyze technically and economically biogas from water hyacinth with cow manure stater. This research was carried out through several stages, namely: preparation of raw materials, stater and plastic biogas digester and techno-economic analysis. In this study the ratio of raw material 1: 1 (water hyacinth chopped 20 kg, water 20 kg) and the addition of stater cattle dung 6 kg. The results of this study are that the technical aspects of biogas start production after 10 days of filling the digester at pH 7.1. Biogas produced is known by direct flame test. Visible on the 10th day the resulting flame is still small, but this shows that the gas has been formed. The pH of the digester is between 4.7 and 8.5. The decrease in TS value from the inlet which is 46 kg to the outlet is 28 kg, indicating that there has been degradation in the substrate in the digester. On the economical aspect the investment cost of a biogas installation in a synthetic digester is IDR 1,500,000.00. Variable costs are the cost of water hyacinth, cow dung and water of Rp 150,000.00 per year. The Cost of Biogas Production is Rp 3,836.08 and if it is sold at a margin of 50% the selling price is Rp 5,800. The break even point in kilograms is 267.2 and in rupiahs is Rp 1.025,000.00. This payback period for investment in biogas business is 2.86 years.